Stability Improvements in a Rail-to-Rail Input/Output, Constant Gm Operational Amplifier, at 0.4 V Operation, Using the Low-Voltage DTMOS Technique - Correia, Joana (2018)
The use of the dynamic threshold MOS (DTMOS) technique is evaluated in a two-stage rail-to-rail Input/Output, constant G m amplifier. The proper choice of specific transistors in which the technique should be used is presented, as well as the resulting improvements, mainly regarding stability of the circuit at low voltage operation. The DTMOS technique is used in the NMOS transistors of the folded-cascode input stage, allowing the circuit to be stable at V DD = 0.4 V, with equivalent gain and gain-and-bandwidth product (GBW) values achieved with the same V DD value, for the initial circuit operating at 0.8 V. The implemented changes allow the circuit to be stable at low voltage operations without requiring any increase in the cascoded-Miller compensation capacitors, saving circuit area and, consequently, cost.